Intrashell Variability of Trace Elements in Benthic Foraminifera Grown Under High CO2 Levels - Levi, Adam; Müller, Wolfgang; Erez, Jonathan (Frontiers in Earth Science, 2019)
Two species of Amphistegina were cultured under four variable DIC concentrations (2340-2570 M). The variability of trace element within the foraminiferal shells was measured in the knob area of three individuals for each DIC treatment using LA-ICPMS. In individuals that showed significant growth (identified via 135Ba-enriched seawater), B, Na and Sr showed an increase with DIC, while K and Mg were slightly lower or unchanged. Sharp transition zones between natural 135Ba and the ~tenfold increased 135Ba in the shells represent one quarter of a new additional chamber, which occurs roughly once a week. The shape of the transition zone is best described by a logistic equation for population growth. We propose that this reflects the dynamics of seawater vacuoles that serve the biomineralization process and provide Ca and DIC for calcification of Amphistegina as described in previous publications (e.g. Bentov et al., 2009). LA-ICPMS profiles in the central knob (~70 µm depth) also revealed previously described cyclical changes in concentration of Mg, each apparently representing a growth of a new chamber. Additional elements such as K, Na and U showed similar cycles with the same frequency and phase as the Mg cycles. Sr showed variability with similar frequency but not in-phase to those of the Mg. These multi-element cycles were found both in the newly grown calcite (elevated-135Ba) and in the natural skeleton regardless of the DIC treatments. These high Mg and multi-element cycles seem to be an essential part of the calcification process. They may originate from the interaction with the organic matrix resulting in elevated Mg and other elements in primary calcite while secondary calcite of the lamination process shows lower concentrations. It is also possible that primary calcite is enriched in trace elements if an Amorphous CaCO3 (ACC) or vaterite precursors are involved. In addition, Rayleigh fractionation from a semi-closed reservoir, the presence of high Mg in the lattice or any combination of the previous causes may explain the trace elements enrichment. Changes in the DIC did not affect the pattern of elemental cycles in these foraminifera, suggesting that this variability is inherent to the biomineralization process.